Effects of combined electromyostimulation and gymnastics training in prepubertal girls - Deley, G.; Cometti, C.; Fatnassi, A.; Paizis, C.; Babault, N. (The Journal of Strength and Conditioning Research, 2011)
This study investigated the effects of a 6-week combined electromyostimulation (EMS) and gymnastic training program on muscle strength and vertical jump performance of prepubertal gymnasts. Sixteen young women gymnasts (age 12.4 ± 1.2 yrs) participated in this study, with 8 in the EMS group and the remaining 8 as controls. EMS was conducted on knee extensor muscles for 20 minutes 3 times a week during the first 3 weeks and once a week during the last 3 weeks. Gymnasts from both groups underwent similar gymnastics training 5-6 times a week. Isokinetic torque of the knee extensors was determined at different eccentric and concentric angular velocities ranging from -60 to +240° per second. Jumping ability was evaluated using squat jump (SJ), counter movement jump (CMJ), reactivity test, and 3 gymnastic-specific jumps. After the first 3 weeks of EMS, maximal voluntary torque was increased (+40.0 ± 10.0%, +35.3 ± 11.8%, and +50.6 ± 7.7% for -60, +60, and +240°/s, respectively; p < 0.05), as well as SJ, reactivity test and specific jump performances (+20.9 ± 8.3%, +20.4 ± 26.2% and +14.9 ± 17.2% respectively; p < 0.05). Six weeks of EMS were necessary to improve the CMJ (+10.1 ± 10.0%, p < 0.05). Improvements in jump ability were still maintained 1 month after the end of the EMS training program. To conclude, these results first demonstrate that in prepubertal gymnasts, a 6-week EMS program, combined with the daily gymnastic training, induced significant increases both in knee extensor muscle strength and nonspecific and some specific jump performances.